The effect of stretching techniques on flexibility and sports injuries: A literature review - Ihsan, Fadli; Karyono, Tri Hadi; Primasoni, Nawan; Kurniawan, Faidillah; Herwin, Herwin; Alim, Abdul; Budiarti, Ratna; Sriwahyuniati, Christina Fajar; Irianto, Subagyo (Jorpres (Jurnal Olahraga Prestasi), 2023)
Flexibility and injury prevention are essential aspects of athlete performance and health. This article aims to present a literature review on the effect of stretching techniques on flexibility and sports injuries. The literature review was conducted by analyzing relevant previously published studies.The literature review identified factors influencing flexibility, including age, gender, and type of sports activity. The literature review also highlighted the benefits of stretching in improving flexibility and preventing sports injuries. Various approaches to stretching techniques were discussed, such as static stretching, dynamic stretching, PNF (Proprioceptive Neuromuscular Facilitation), and other methods.However, there is controversy surrounding the effectiveness of stretching in preventing sports injuries. Some studies suggest that pre-exercise stretching can reduce the risk of injury, while others suggest that excessive static stretching can reduce muscle strength and exercise performance.The results from the literature review also highlighted the differences in research results regarding the effect of stretching on flexibility and injury. Some studies found a positive association between stretching and increased flexibility, while the results of other studies showed no significant association.In the discussion, this article analyzes the advantages and disadvantages of stretching techniques found in the literature. The implications of these findings can help coaches and athletes design efficacious and safe stretching programs.In conclusion, stretching techniques are essential in improving flexibility and may affect preventing sports injuries. However, more research is needed to understand better the mechanisms of stretching techniques' effects on flexibility and sports injuries. Hopefully, this article can provide valuable insights for sports practitioners and researchers to understand better the role of stretching in sports and athlete health.